2003
DOI: 10.1211/0022357021035
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical strategies to prevent ventilator-associated pneumonia

Abstract: The increasing incidence of hospital-acquired (nosocomial) infection is a disturbing phenomenon resulting in significant patient mortality and putting considerable strain on healthcare budgets and personnel. One particularly serious aspect of nosocomial infection is that of ventilator-associated pneumonia (VAP). This arises in patients who receive mechanical ventilation within the intensive care unit. The quoted incidence of VAP varies widely (5-67%) and the reported mortality of patients with VAP is in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 166 publications
0
13
0
Order By: Relevance
“…Different studies reported varied VAP incidence rates ranging from 5% to 67%, which may be confounded by the presence of mixed populations with variable age groups, underlying conditions, other associated risk factors, and using different gold standards for diagnosis 16. The National Nosocomial Infections Surveillance System of the CDC reported the median rate of VAP cases per 1,000 MVD in the US was higher in SICUs (range 6.2–11.4) than in medical ICUs (3.7) 17.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies reported varied VAP incidence rates ranging from 5% to 67%, which may be confounded by the presence of mixed populations with variable age groups, underlying conditions, other associated risk factors, and using different gold standards for diagnosis 16. The National Nosocomial Infections Surveillance System of the CDC reported the median rate of VAP cases per 1,000 MVD in the US was higher in SICUs (range 6.2–11.4) than in medical ICUs (3.7) 17.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus and Ps. aeruginosa have emerged as the principal causative organisms of ventilator-associated pneumonia 48,49 . Therefore clinical isolates of these pathogens were selected to evaluate the antimicrobial properties of the candidate hydrogels.…”
Section: Antimicrobial and Microbial Anti-adherence Properties Of Hydmentioning
confidence: 99%
“…Medical device related infection is common to all medical devices and results following attachment of pathogenic bacteria onto the outer surface or lumen of the medical device. Bacteria may then adopt a biofilm growth mode, dislodge from the biofilm and initiate infection in the surrounding tissue [1,[3][4][5]. Encrustation involves the deposition of crystalline deposits onto the outer surface/lumen of urinary medical devices and is frequently due to bacterial alkalisation of the urine [1,6].…”
Section: Introductionmentioning
confidence: 99%